Preparation method and application of SERS substrate based on Ni-NiO composite nanostructure

CN122922022APending Publication Date: 2026-10-16BEIJING INFORMATION SCI & TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611117501.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

例如,电子束光刻技术能够制备尺寸与间距精确可控的金属纳米棱镜阵列作为高均匀性的SERS基底;化学气相沉积技术可用于制备石墨烯包裹的金属颗粒复合结构;超短飞秒脉冲激光加工技术也可用于SERS基底的制备,然而,上述方法存在制备工艺复杂、成本高昂且无法批量生产等缺点,限制了SERS技术在实际应用中的推广

Benefits of technology

本发明采用金属Ni与NiO构建同源复合纳米结构作为SERS基底,大幅降低了材料成本并提升了生物相容性,操作简便、具有良好的灵敏度、增强效果、重复性和均匀性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122922022A_ABST
    Figure CN122922022A_ABST
Patent Text Reader

Abstract

The application discloses a kind of based on Ni-NiO composite nanostructure SERS substrate preparation method and its application, the SERS substrate includes: Ni sheet substrate and the Ni-NiO composite nanofilm loaded on the surface of Ni sheet substrate, the Ni-NiO composite nanofilm is composed of Ni nanoparticle and NiO nanoparticle mixture.This application uses metal Ni and NiO to construct homologous composite nanostructure as SERS substrate, greatly reduce the material cost and improve biocompatibility, easy to operate, with good sensitivity, enhancement effect, repeatability and uniformity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of SERS substrate technology, and in particular to a method for preparing and applying SERS substrates based on Ni-NiO composite nanostructures. Background Technology

[0002] Surface-enhanced Raman scattering (SERS) technology can provide characteristic fingerprint spectral information of molecules under test, which has important application value in the field of optical sensing. Various SERS substrate fabrication processes have been developed. For example, electron beam lithography can fabricate metal nanoprism arrays with precisely controllable size and spacing as highly uniform SERS substrates; chemical vapor deposition can be used to prepare graphene-encapsulated metal particle composite structures; and ultrashort femtosecond pulse laser processing technology can also be used to prepare SERS substrates. However, the above methods have disadvantages such as complex fabrication processes, high costs, and inability to mass-produce, which limits the promotion of SERS technology in practical applications.

[0003] Existing SERS substrates mostly employ noble metal nanostructures such as gold and silver, due to their low detection limits, which can even enable single-molecule detection. For example, SERS substrates using two-dimensional hydrogen-bonded organic frameworks loaded with gold nanoparticles can achieve the detection of antibiotic molecules; Fe3O4@Ag nanoparticles with core-shell structures can also be used as SERS substrates for the detection of heavy metal ions in environmental water. However, noble metal-based SERS substrates generally suffer from high material costs and complex preparation processes, and the biocompatibility and long-term stability of some systems are limited, restricting their application as biomolecular sensing materials.

[0004] To overcome the aforementioned problems, researchers have begun to focus on the development of non-noble metal SERS substrates. Semiconductor materials have advantages such as tunable band gaps, high catalytic activity, and low cost. Existing research shows that SERS substrates based on non-noble metal nanomaterials such as carbon, titanium, zinc, copper, molybdenum, and tungsten have good economic efficiency and stability. Transition metal oxides are also considered as candidate materials for SERS substrates. Taking nickel-based materials as an example, existing research involves the SERS application of NiO thin films, as well as the preparation and SERS performance of fullerene-like structured nickel hydroxychloride nanospheres. However, most nickel-based SERS substrates still rely on strategies of composite with noble metals, such as Ag@Ni core-shell nanoparticles, Au / nickel foam composite substrates, and NiO microflower structures modified with silver nanoparticles. These require the electromagnetic field enhancement effect of noble metals to obtain high SERS activity. Research on nickel-based SERS substrates without noble metals is still very limited, and there is still considerable room for improvement in their SERS enhancement effect and detection sensitivity.

[0005] Furthermore, existing methods for preparing non-noble metal SERS substrates also have many limitations. Micro-nano fabrication technology involves expensive equipment, complex processes, and is difficult to scale up. Even with the relatively simple ultrasonic dispersion combined with spin-coating film formation process, it is currently mainly applied to single metal nanoparticle systems or metal-noble metal composite systems. There are no reports of applying this process to non-noble metal homologous composite systems and achieving excellent SERS performance. In summary, existing SERS substrate technologies suffer from the following shortcomings: First, noble metal-based SERS substrate materials are costly, and their biocompatibility and long-term stability are limited. Second, high-precision micro / nano fabrication techniques are complex, costly, and difficult to mass-produce. Third, most existing non-noble metal SERS substrates, especially nickel-based systems, still require composite with noble metals to achieve the desired reinforcement effect. Fourth, existing SERS substrates prepared by ultrasonic-assisted spin coating methods do not yet involve non-noble metal homologous composite systems. Therefore, a method for preparing SERS substrates based on Ni-NiO composite nanostructures and its applications are needed. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing SERS substrates based on Ni-NiO composite nanostructures and their applications, so as to solve the problems existing in the prior art. To achieve the above objectives, the present invention is implemented according to the following technical solution: The first aspect of the present invention provides a SERS substrate based on a Ni-NiO composite nanostructure, the SERS substrate comprising: a Ni sheet substrate and a Ni-NiO composite nanofilm loaded on the surface of the Ni sheet substrate, the Ni-NiO composite nanofilm being composed of a mixture of Ni nanoparticles and NiO nanoparticles, wherein the mass ratio of Ni powder to NiO powder is 1:1.

[0007] Furthermore, the Ni nanoparticles and NiO nanoparticles have a particle size distribution range of 50 nm to 250 nm, with an average particle size of 150 nm.

[0008] On the other hand, a method for preparing a SERS substrate based on a Ni-NiO composite nanostructure includes the following steps: The Ni wafers are pretreated to obtain clean Ni wafers; Ni powder and NiO powder are added to anhydrous ethanol for ultrasonic dispersion treatment. The mass ratio of Ni powder to NiO powder is 1:1, so that Ni nanoparticles and NiO nanoparticles are evenly dispersed in anhydrous ethanol. During the ultrasonic dispersion treatment, a dispersant is added to the solution in small amounts multiple times to form a nano solution. The nanosolution is deposited on the clean Ni wafer surface by spin coating, and after drying, a Ni-NiO composite nanofilm is formed, which is the SERS substrate.

[0009] Furthermore, the dispersant is methyl methacrylate, and the mass fraction of methyl methacrylate is 1%.

[0010] Furthermore, the pretreatment of the Ni sheet includes: ultrasonically cleaning the Ni sheet in acetone, anhydrous ethanol and deionized water for 15 minutes in sequence, and then drying it under a high-purity nitrogen gas flow.

[0011] Furthermore, the ultrasonic dispersion time is 20 minutes.

[0012] Furthermore, the spin coating process parameters are: rotation speed 3000 r / min, time 30 seconds; the spin coating operation is repeated 3 to 5 times, and the amount of nano solution used is 100 μL per spin coating.

[0013] Furthermore, a surface-enhanced Raman scattering detection method includes the following steps: Provide a SERS substrate based on a Ni-NiO composite nanostructure as described in claim 1 or 2; The sample solution to be tested was drop-coated onto the surface of the SERS substrate and dried at room temperature. Raman spectroscopy was used to perform Raman spectroscopy on the dried SERS substrate to obtain the SERS signal of the sample.

[0014] Furthermore, the excitation wavelength for the Raman spectroscopy test was 785 nm, the laser power was 50 mW, and the spectral acquisition time was 10 s.

[0015] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects: This invention uses a homologous composite nanostructure constructed from metallic Ni and NiO as a SERS substrate, which significantly reduces material costs and improves biocompatibility. It is easy to operate and has good sensitivity, enhancement effect, repeatability and uniformity. Attached Figure Description

[0016] Figure 1 The flowchart and XRD pattern of the Ni-NiO composite nanostructure SERS substrate prepared in this invention are shown. in, Figure 1 (a) is a schematic diagram of the SERS substrate preparation process; Figure 1 (b) The XRD pattern of the prepared SERS substrate; Figure 2 This is a schematic diagram of the Raman testing apparatus used in the SERS test of this invention; Figure 3 The morphology characterization results of the Ni-NiO composite nanostructure SERS substrate prepared in this invention are shown. in, Figure 3 (a) A scanning electron microscope (SEM) image of the prepared substrate; Figure 3 (b) is a statistical histogram of the particle size distribution of Ni-NiO nanoparticles; Figure 3 (c) is a schematic diagram of the structure of the prepared substrate; Figure 4 A comparison of the SERS strength of two groups of SERS substrates with and without MMA dispersant; Figure 5 The image shows a comparison of the SERS intensity of the Raman characteristic peak at 1361 cm⁻¹ between the Ni-NiO composite substrate and the pure Ni substrate in R6G solutions of different concentrations. Figure 6 This is the SERS plot used in the present invention for calculating the enhancement factor (EF); in, Figure 6 (a) Testing of clean Ni sheets at 1×10 -2 SERS spectrum of mol / LR6G; Figure 6 (b) Detection of Ni-NiO composite substrate at 1×10 -6 SERS spectrum of mol / LR6G; Figure 7 The SERS spectra of the Ni-NiO composite nanostructure SERS substrate prepared in this invention against R6G solutions of different concentrations are shown. Figure 8 The results show the repeatability test results of the Ni-NiO composite nanostructure SERS substrate prepared in this invention. in, Figure 8 (a) SERS spectra of 10 randomly selected points on the same sample; Figure 8 (b) is 1361cm -1 Statistical histogram of Raman intensity at the location; Detailed Implementation

[0017] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0018] Example 1: Preparation of Ni-NiO composite nanostructure SERS substrate This embodiment provides a method for preparing a surface-enhanced Raman scattering (SERS) substrate based on a Ni-NiO composite nanostructure. The specific steps are as follows: (1) Ni wafer pretreatment The Ni sheet was sequentially placed in acetone, anhydrous ethanol, and deionized water, and ultrasonically cleaned for 15 minutes in each solution to remove oil and impurities from the surface of the Ni sheet. After cleaning, the Ni sheet was dried under a high-purity nitrogen stream to obtain a clean Ni sheet for later use.

[0019] (2) Preparation of nano solutions Weigh 0.01g of Ni powder and 0.01g of NiO powder (Ni powder to NiO powder mass ratio 1:1), and add them to 50mL of anhydrous ethanol to form a mixed nano-solution. Place the container containing this nano-solution in an ultrasonic machine and perform ultrasonic dispersion treatment for 20 minutes. During the ultrasonic dispersion treatment, add 1% (w / w) methyl methacrylate (MMA) dispersant to the solution in small amounts multiple times to ensure that the Ni nanoparticles and NiO nanoparticles are fully and uniformly dispersed in the anhydrous ethanol. After ultrasonic dispersion is completed, a uniformly dispersed nano-solution is obtained.

[0020] (3) Spin coating to form a film Take 100 μL of the nanosolution prepared in step (2) using a pipette and drop it onto the surface of a clean Ni wafer placed in the center of a spin coater. Set the spin coater speed to 3000 r / min and the spin coat time to 30 seconds. Repeat the above spin coat operation 3 to 5 times to form a uniform nanofilm of Ni-NiO nanoparticles on the surface of the Ni wafer. Allow the spin-coated Ni wafer to air dry at room temperature to obtain the Ni-NiO composite nanostructure SERS substrate.

[0021] Figure 1 (a) shows a schematic diagram of the preparation process of the SERS substrate in this embodiment.

[0022] Example 2: Morphological characterization of Ni-NiO composite nanostructure SERS substrate The Ni-NiO composite nanostructure SERS substrate prepared in Example 1 was characterized by scanning electron microscopy (SEM). Figure 3 (a) It can be seen that the prepared Ni-NiO composite SERS substrate is mainly composed of spherical nanoparticles with a particle size distribution ranging from 50 nm to 250 nm. The particle size was statistically analyzed using Nano Measurement software to obtain the size distribution law of the Ni-NiO nanoparticles, and the corresponding particle size distribution histogram was plotted. The results are shown below. Figure 3As shown in (b). Statistical results indicate that the average particle size of Ni nanoparticles and NiO nanoparticles is approximately 150 nm. Based on the above SEM morphology observations, a schematic diagram of the Ni-NiO composite substrate was constructed, as shown below. Figure 3 As shown in (c).

[0023] Example 3: Phase analysis of Ni-NiO composite nanostructure SERS substrate The Ni-NiO composite nanostructure SERS substrate prepared in Example 1 was characterized by X-ray diffraction (XRD). Figure 1 (b) It can be seen that no diffraction peaks of other substances were detected on the substrate. The XRD pattern only showed characteristic diffraction peaks belonging to Ni and NiO, indicating that the prepared substrate contained only Ni and NiO phases and no other impurity phases.

[0024] Example 4: SERS activity test of Ni-NiO composite nanostructure SERS substrate Rhodamine 6G (R6G) was used as a probe molecule to evaluate the SERS activity of the Ni-NiO composite nanostructure SERS substrate prepared in Example 1. A concentration of 10⁻⁻⁶ was prepared by stepwise dilution. 4 mol / L~10⁻ 7 A mol / L aqueous solution of R6G was prepared. 20 μL of the R6G aqueous solution was pipetted onto the prepared SERS substrate and allowed to dry naturally at room temperature before SERS testing.

[0025] Raman spectra were obtained using a microconfocal Raman spectrometer. The spectrometer parameters were set as follows: excitation wavelength 785 nm, laser power 50 mW, spectral acquisition time 10 s, and objective lens magnification 50x. The Raman testing setup is as follows: Figure 2 As shown.

[0026] Example 5: Effect of MMA dispersant on SERS activity To investigate the effect of adding methyl methacrylate (MMA) dispersant on the SERS activity of the substrate, two sets of comparative experiments were designed in this example. The first set of substrates was prepared with MMA dispersant added according to the method in Example 1, while the second set of substrates was prepared without MMA dispersant added, and the remaining experimental conditions were completely consistent with those in Example 1.

[0027] Subsequently, using R6G molecules as probe molecules, the two sets of SERS substrates were compared for their response to R6G molecules at 1361 cm⁻¹. -1 The SERS intensity at the Raman shift. The measured Raman spectrum is as follows. Figure 4As shown in the figure. The results indicate that the SERS intensity of the substrate prepared with MMA was nearly 1.3 times higher than that of the substrate without MMA, suggesting that adding MMA during the preparation process can significantly improve the SERS activity of the substrate.

[0028] Example 6: Comparison of SERS activity between Ni-NiO composite substrate and pure Ni substrate To further verify the synergistic advantages of the Ni-NiO composite system in SERS enhancement, this embodiment designed a pure Ni nanosubstrate as a control group for comparative experiments. The pure Ni substrate was prepared using the same standardized spin-coating process as in Example 1, the only difference being that NiO powder was not added to the nanosolution; that is, only Ni powder was used to prepare a pure Ni nanosolution before spin-coating.

[0029] Subsequently, the system compared the Ni-NiO composite substrate and the pure Ni substrate at different concentrations (10). -4 mol / L, 10 -5 mol / L and 10 -6 In R6G solution (mol / L), 1361 cm -1 The absolute SERS intensity of the Raman characteristic peak. The results are as follows: Figure 5 As shown, the experimental results indicate that the Raman signal intensity of the pure Ni substrate is weak, and it exhibits a significant sensitivity bottleneck at low concentrations. In contrast, the Ni-NiO composite substrate outperforms the single metallic Ni substrate in both absolute signal amplification and trace detection capability.

[0030] Example 7: Calculation of the enhancement factor of Ni-NiO composite nanostructure SERS substrate The enhancement factor (EF) is an important indicator for evaluating the performance of SERS substrates. In this embodiment, the enhancement factor of the prepared Ni-NiO composite nanostructure SERS substrate was calculated according to the following method.

[0031] Design two sets of comparative experiments: First group of experiments: 1×10 -6 A mol / L R6G solution was drop-coated onto the surface of the Ni-NiO composite substrate prepared in Example 1. After air drying at room temperature, Raman spectra were measured using a Raman spectrometer. The results are as follows: Figure 6 As shown in (b).

[0032] Second group of experiments: 1×10 -2 A mol / L R6G solution was drop-coated onto the surface of a clean Ni wafer. After air drying at room temperature, the Raman spectrum was measured using a Raman spectrometer. The results are as follows: Figure 6 As shown in (a).

[0033] With 1361cm -1Taking the Raman intensity at a certain point as the research object, the enhancement factor of the substrate is calculated according to the following formula:

[0034] in, This indicates adsorption on a Ni-NiO substrate of 1×10 -6 SERS intensity of R6G at mol / L; Indicates 1×10 on the Ni film -2 SERS intensity of R6G at mol / L; This indicates the concentration of R6G on the Ni sheet. This indicates the concentration of R6G on the Ni-NiO substrate.

[0035] According to equation (1), the enhancement factor of the substrate can be calculated to be approximately 3.83 × 10⁻⁶. 5 This indicates that the substrate exhibits a good SERS enhancement effect.

[0036] Example 8: Sensitivity testing of Ni-NiO composite nanostructure SERS substrate To evaluate the quantitative detection capability of the prepared Ni-NiO composite nanostructure SERS substrate for R6G molecules, a concentration of 10 was prepared. -4 mol / L~10 -7 A mol / L aqueous solution of R6G was drop-coated onto the substrate surface for SERS testing. The results are as follows: Figure 7 As shown, the SERS intensity of each characteristic peak gradually decreases with decreasing target molecule concentration. When the analyte concentration is as low as 1×10⁻⁶, the intensity of the peak decreases further. -7 Even at mol / L, the characteristic peak of R6G can still be clearly identified. The above results indicate that the prepared Ni-NiO composite substrate has good sensitivity and has good application prospects in trace detection.

[0037] Example 9: Repeatability testing of Ni-NiO composite nanostructure SERS substrate To evaluate the repeatability and uniformity of the prepared Ni-NiO composite nanostructure SERS substrate, SERS measurements were performed at 10 randomly selected points on the same sample. The test sample was 1×10⁻⁶. -5 The SERS spectrum collected for an R6G solution with a concentration of mol / L is as follows: Figure 8 As shown in (a), the SERS intensities of the characteristic peaks at the 10 collected spectra are almost identical, indicating good homogeneity of the substrate at different locations. For example, R6G at 1361 cm⁻¹... -1 Taking the characteristic peak at a certain location as the object, its SERS intensity is plotted as a statistical graph, such as... Figure 8As shown in (b), the relative standard deviation (RSD) of the 10 measurement points on the substrate was calculated to be 10.08%. The above results indicate that the SERS substrate prepared in this embodiment using Ni and NiO as materials has good repeatability and uniformity.

[0038] Example 10: Application of Ni-NiO composite nanostructure SERS substrate in trace molecular detection The Ni-NiO composite nanostructure SERS substrate prepared in Example 1 was used for SERS detection of trace molecules. The specific method was as follows: the sample solution to be tested (such as R6G aqueous solution or other target molecule solution) was drop-coated onto the surface of the prepared SERS substrate. After natural drying at room temperature, Raman spectroscopy was performed using a microconfocal Raman spectrometer. The test parameters were: excitation wavelength 785 nm, laser power 50 mW, spectral acquisition time 10 s, and objective lens magnification 50x. By analyzing the characteristic peak information of the obtained Raman spectrum, qualitative and / or quantitative detection of the trace molecules to be tested was achieved.

[0039] Example 11: Extension of other metal-semiconductor composite systems The nanostructures described in this invention are not limited to the Ni-NiO system, but can also be extended to other homologous metal-semiconductor composite systems, such as the Ag-NiO system. Taking the Ag-NiO system as an example, the Ag-NiO composite nanostructure SERS substrate can be prepared using a method basically the same as in Example 1, the only difference being that Ni powder is replaced with Ag powder, the Ni sheet substrate is replaced with an Ag sheet substrate, and the process parameters are adjusted accordingly.

[0040] The above description is merely an example and illustration of the structure of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the structure of the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.

Claims

1. A SERS substrate based on a Ni-NiO composite nanostructure, characterized in that, The SERS substrate includes a Ni sheet substrate and a Ni-NiO composite nanofilm loaded on the surface of the Ni sheet substrate. The Ni-NiO composite nanofilm is composed of a mixture of Ni nanoparticles and NiO nanoparticles, and the mass ratio of Ni powder to NiO powder is 1:

1.

2. The SERS substrate based on the Ni-NiO composite nanostructure according to claim 1, characterized in that, The Ni nanoparticles and NiO nanoparticles have a particle size distribution range of 50 nm to 250 nm, with an average particle size of 150 nm.

3. A method for preparing a SERS substrate based on a Ni-NiO composite nanostructure as described in claim 1 or 2, characterized in that, Includes the following steps: The Ni wafers are pretreated to obtain clean Ni wafers; Ni powder and NiO powder are added to anhydrous ethanol for ultrasonic dispersion treatment. The mass ratio of Ni powder to NiO powder is 1:1, so that Ni nanoparticles and NiO nanoparticles are evenly dispersed in anhydrous ethanol. During the ultrasonic dispersion treatment, a dispersant is added to the solution in small amounts multiple times to form a nano solution. The nanosolution is deposited on the clean Ni wafer surface by spin coating, and after drying, a Ni-NiO composite nanofilm is formed, which is the SERS substrate.

4. The preparation method according to claim 3, characterized in that, The dispersant is methyl methacrylate, and the mass fraction of methyl methacrylate is 1%.

5. The preparation method according to claim 3, characterized in that, The pretreatment of the Ni sheet includes: ultrasonically cleaning the Ni sheet in acetone, anhydrous ethanol and deionized water for 15 minutes in sequence, and then drying it under a high-purity nitrogen gas flow.

6. The preparation method according to claim 3, characterized in that, The ultrasonic dispersion time is 20 minutes.

7. The preparation method according to claim 3, characterized in that, The spin coating process parameters are: rotation speed 3000 r / min, time 30 seconds; the spin coating operation is repeated 3 to 5 times, and the amount of nano solution used is 100 μL for each spin coating.

8. A surface-enhanced Raman scattering detection method, characterized in that, Includes the following steps: Provide a SERS substrate based on a Ni-NiO composite nanostructure as described in claim 1 or 2; The sample solution to be tested was drop-coated onto the surface of the SERS substrate and dried at room temperature. Raman spectroscopy was used to perform Raman spectroscopy on the dried SERS substrate to obtain the SERS signal of the sample.

9. The surface-enhanced Raman scattering detection method according to claim 8, characterized in that, The excitation wavelength for the Raman spectroscopy test was 785 nm, the laser power was 50 mW, and the spectral acquisition time was 10 s.